Meningkatkan Hasil Belajar Siswa Kelas VIIIB SMP Negeri 1 Amuntai Melalui Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) - Santi Minati Adi; M. Arifuddin Jamal; Sri Hartini (Berkala Ilmiah Pendidikan Fisika, 2015)
One cause of low student learning outcomes are due to the model used by teachers is still less varied so that impact on student learning outcomes. Therefore a research was conducted aimed at improving student learning outcomes through cooperative learning model NHT. The specific objective of this study to describe: (1) adherence to the RPP; (2) social skills of students; (3) the results of student learning. This type of research is PTK Hopkins models consist of 3 cycles, covering planning, observation and observation, and reflection. Data obtained through observation, testing, and documentation. Data were analyzed descriptively qualitative and quantitative. The results showed: (1) adherence to the RPP in the first cycle 68% (good), the second cycle 82% (very good), and the third cycle 86% (very good); (2) social skills of students in the first cycle was in good category except the fourth aspect fifth category is still lacking, the second cycle of all aspects of a good category except the fourth and fifth aspects very well except category, and the third cycle of all aspects of excellent category, except the second aspect still categorized as good; (3) the results of student learning classical first cycle of 44% (completed), the second cycle of 77% (completed), and the third cycle of 88% (completed). It can be  concluded that the implementation of cooperative learning model NHT can improve student learning outcomes in a way more motivating teachers to participate in each learning.